Long-term results of a protocol-based ultrasound-guided salvage brachytherapy as re-irradiation for local recurrent prostate cancer - Schönle, Nicole; Strnad, Vratislav; Lotter, Michael; Kreppner, Stephan; Fietkau, Rainer (Radiotherapy and Oncology, 2020)
Background and purpose: To assess the long-term results of protocol-based ultrasound-guided salvage pulsed-dose rate brachytherapy in locally recurrent prostate cancer following previous radiation therapy. Materials and methods: A total of 82 patients (median age 69 years) with locally recurrent prostate cancer after previous external beam radiation therapy (43/82, 52.4%), prostatectomy and adjuvant radiation therapy (24/82, 29.3%) or brachytherapy (15/82, 18.3%) were treated with sole salvage interstitial pulsed-dose rate brachytherapy (PDR-BT). The treatment regimen consisted of two PDR-BT sections with 30 Gy (single pulse dose 0.6 Gy/h, 24 h per day) each up to a total reference dose of 60 Gy (EQD2 = 71.5 Gy-eq). The endpoints of the present analysis are cumulative local recurrence-rate, PSA-free survival, overall survival and the treatment-associated late toxicity according to the “Common Toxicity Criteria” with a median follow-up of 49 months (range, 12–129 months). Results: The 5-y. overall cumulative local recurrence rate was 17.7% with no significant differences between low, intermediate and high-risk groups. Differences in PSA-free survival were marginally non-significant, at 67.3%, 70.4% and 63.8% for low, intermediate and high risk group, respectively. No grade 3 gastrointestinal late side effects have been observed. The most common late side effect was urinary incontinence grade 1–3 and urinary frequency/urgency grade 1–3 in 18.3% (15/82) and 17.1% (14/82) of patients, respectively. Conclusion: PDR salvage brachytherapy in local recurrent previously irradiated prostate cancer is efficient with low late toxicity. Salvage-brachytherapy represents a valuable therapeutic option for the treatment of previously irradiated locally recurrent prostate cancer.
CRIS-Team Scopus Importer:2020-07-24
Keywords: Prostate cancer; Re-irradiation; Salvage-brachytherapy